Emerging Energetic Materials: Synthesis, Physicochemical, and Detonation Properties - Viswanath, Dabir S. (Springer Netherlands, 2018)
This book summarizes science and technology of a new generation of high-energy and insensitive explosives. The objective is to provide professionals with comprehensive information on the synthesis and the physicochemical and detonation properties of the explosives. Potential technologies applicable for treatment of contaminated waste streams from manufacturing facilities and environmental matrices are also be included. This book provides the reader an insight into the depth and breadth of theoretical and empirical models and experimental techniques currently being developed in the field of energetic materials. It presents the latest research by DoD engineers and scientists, and some of DoD's academic and industrial researcher partners. The topics explored and the simulations developed or modified for the purposes of energetics may find application in other closely related fields, such as the pharmaceutical industry. One of the key features of the book is the treatment of wastewaters generated during manufacturing of these energetic materials.